Educação sexual no ambiente escolar - Lucas José Silva Costa (2021)
The teaching of science in schools has been changing over the years. Traditional teaching methods, especially those based on the transmission of content, no longer have the same appeal to the student body as they once did. The use of new teaching strategies, such as those based on the STEAM (Science, Technology, Engineering, Arts and Mathematics) or CTS (Science, Technology and Society) approach brings with it an interdisciplinary and investigative bias. Giving significance to the learning processes is fundamental, therefore, working on topics of interest to the student, such as sexual and reproductive health, can result in an improvement in the quality of life. The emergence of new cases of sexually transmitted infections (STIs) such as AIDS (acquired human immunodeficiency syndrome) demonstrates the need to discuss sex education in the school context. Therefore, the present work proposes the application of a didactic sequence (DS) with activities that relate the biological role of the human being in reproduction and its nuances, such as STIs and gender relations. This theme enabled the application of investigative activities related to the incidence of STIs, resulting in the elaboration of a printed booklet focused on the prevention of such infections, together with the construction of a game, whose purpose is to test the player's knowledge about the consequences of STIs, such as AIDS. During the implementation of the proposed activities, it was noticed that the participation and involvement of the students remained constant. It was observed that the activities proposed in the SD corresponded to the objectives and answered the researcher's guiding questions. It was also possible to perceive that the use of active teaching methodologies offers the student the opportunity to investigate and lead the construction of their own knowledge. Thus, it was possible to verify that actions related to the learning of content related to sex education in schools are extremely necessary. The application of interactive and investigative activities allowed the teacher to explore teaching methodologies capable of instigating the student, who was not limited to the mere role of content receiver. The topic of sex education, focused on human reproduction, STIs and gender relations, was in line with the students' wishes for the search for information in this area, since the topic is usually not discussed broadly in other contexts, such as the family. Finally, the publication of the SD produced and used for the development of this work may help other teachers who have the desire to work on the themes explained here.